Performance evaluation and international transfer pricing in foreign subsidiaries of Japanese companies / Li Jingna, Dyna Seng Kate and Wynn-Williams - Li, Jingna; Dyna, Seng Kate; Wynn, Williams (Accounting Research Institute (ARI), 2011)
This paper aims to analyse the results of a questionnaire survey concerning international transfer pricing and performance evaluation in foreign subsidiaries of Japanese companies. Sato (1991) provided the foundation questions for this survey, and several different results from those of Sato (1991) have become apparent, for example: changes in the purposes for which Japanese companies establish and maintain foreign subsidiaries; the increased importance of performance evaluation of local managers and the use of both financial and non-financial indicators for performance evaluation. The paper also examines who determines the international transfer pricing and explores how it is calculated, including comparisons with Sato (1991) and others. The results show that international transfer pricing is now determined by headquarters under the company policies of maximization of group profits and observance of tax laws, and is calculated using company standards as opposed to taxation standards. The correlation between the purpose of performance evaluation and financial indicators has also been examined. Japanese companies prefer to use financial indicators such as profit and sales for performance evaluation, with less emphasis on financial indicators of capital efficiency such as ROI and ROE. Moreover, Japanese companies do not only depend on financial indicators for performance evaluation, but also on other methods such as non-financial indicators.